2014
DOI: 10.1371/journal.pone.0090989
|View full text |Cite
|
Sign up to set email alerts
|

Deep RNA Sequencing Reveals Hidden Features and Dynamics of Early Gene Transcription in Paramecium bursaria Chlorella Virus 1

Abstract: Paramecium bursaria chlorella virus 1 (PBCV-1) is the prototype of the genus Chlorovirus (family Phycodnaviridae) that infects the unicellular, eukaryotic green alga Chlorella variabilis NC64A. The 331-kb PBCV-1 genome contains 416 major open reading frames. A mRNA-seq approach was used to analyze PBCV-1 transcriptomes at 6 progressive times during the first hour of infection. The alignment of 17 million reads to the PBCV-1 genome allowed the construction of single-base transcriptome maps. Significant transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…The genes encoding these virion-associated proteins are dispersed throughout the virus genome, and most are transcribed late or early-late in the infection cycle. In contrast, the PBCV-1 ANK and vSkp1 genes are expressed as early genes (44,45). Western blotting confirmed the appearance of the vSkp1 PBCV-1 protein at 45 min p.i.…”
Section: Resultsmentioning
confidence: 80%
“…The genes encoding these virion-associated proteins are dispersed throughout the virus genome, and most are transcribed late or early-late in the infection cycle. In contrast, the PBCV-1 ANK and vSkp1 genes are expressed as early genes (44,45). Western blotting confirmed the appearance of the vSkp1 PBCV-1 protein at 45 min p.i.…”
Section: Resultsmentioning
confidence: 80%
“…The ratio of the mean transcript counts of the most expressed viral gene (OtV5_154c: 5,878) over that of one of the most highly expressed host genes, the ribulose bisphosphate carboxylase small subunit ( rbcS , ostta18g01880: 49,249), gives 0.12. As a comparison, the transcript abundance ratio of the corresponding genes during Paramecium bursaria chlorella Virus 1 (PBCV-1) infection of Chlorella was 37, far exceeding host transcription levels [47]. Since relative OtV5 transcription was lower than that of the host, even in R P lines with relatively higher OtV5 transcripts levels, this suggests viral activity was certainly much lower than expected during infection of susceptible O .…”
Section: Resultsmentioning
confidence: 99%
“…Chlorovirus PBCV‐1 infection of Chlorella variabilis is initiated by the ejection of its dsDNA genome into the host cytoplasm in a phage‐like process (Van Etten and Dunigan, ), which is followed by its presumed translocation into the nucleus. Early PBCV‐1 transcription was detected within 7 min post infection (PI) (Blanc et al ., ), followed by viral DNA synthesis at 60 min PI (Van Etten et al ., ). The studies reported here focus on the cytoplasmic factories generated by PBCV‐1 shortly after the release of its replicated genomes from the host nuclei into the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%